Profile of Ameloblastoma from a Retrospective Study in Jakarta, Indonesia - Rusdiana Rusdiana; Sirera Uvie Sandini; Evy Eida Vitria; Teguh Iman Santoso (Faculty of Dentistry, Universitas Indonesia, 2013)
Ameloblastoma is an odontogenic tumor occurring mostly in mandible. Objective: the purpose of the study was to find out the distribution and frequency of the most common histopathological type and pattern of ameloblastoma, the percentage of ameloblastoma according to gender and histopathological types of ameloblas-toma related to gender. Methods: This research was a quantitative analysiswith descriptive retrospective de-sign. This study used secondary data taken from medical records at Oral and Maxillofacial Surgery Clinic of Cipto Mangunkusumo General Hospital Jakarta in the period of January 2002-July 2008. The relationship be-tween age or gender and histopathological types of ameloblastoma was statistically assessed. Results: From data of ameloblastoma patients that have been collected as many as 66 cases; it was found that 31-50 years old age group had the highest percentages of occurrence among other age groups that was 53% from all cases. There are slight differences between women and men in ameloblastoma cases. The incidence was higher in women (37 cases, 56.1%) than in men (29 cases, 43.9%) and the histopathological type found most often was plexiform type as many as 31.8% from all cases. Conclusion: Ameloblastoma presented in adult period, more frequent in women than men, and were predominantly plexiform. DOI: 10.14693/jdi.v18i2.60